Step * 1 of Lemma subsequence-converges


1. : ℝ
2. : ℕ ⟶ ℝ
3. : ℕ ⟶ ℝ
4. N1 : ℕ
5. ∀n:ℕ. ∃m:ℕ((n ≤ m) ∧ (y[n] x[m])) supposing N1 ≤ n
6. ∀k:ℕ+(∃N:{ℕ(∀n:ℕ((N ≤ n)  (|x[n] a| ≤ (r1/r(k)))))})
7. : ℕ+
8. : ℕ
9. ∀n:ℕ((N ≤ n)  (|x[n] a| ≤ (r1/r(k))))
⊢ ∃N:{ℕ(∀n:ℕ((N ≤ n)  (|y[n] a| ≤ (r1/r(k)))))}
BY
(InstConcl [⌜imax(N;N1)⌝]⋅ THEN Auto) }

1
1. : ℝ
2. : ℕ ⟶ ℝ
3. : ℕ ⟶ ℝ
4. N1 : ℕ
5. ∀n:ℕ. ∃m:ℕ((n ≤ m) ∧ (y[n] x[m])) supposing N1 ≤ n
6. ∀k:ℕ+(∃N:{ℕ(∀n:ℕ((N ≤ n)  (|x[n] a| ≤ (r1/r(k)))))})
7. : ℕ+
8. : ℕ
9. ∀n:ℕ((N ≤ n)  (|x[n] a| ≤ (r1/r(k))))
10. : ℕ
11. imax(N;N1) ≤ n
⊢ |y[n] a| ≤ (r1/r(k))


Latex:


Latex:

1.  a  :  \mBbbR{}
2.  x  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
3.  y  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
4.  N1  :  \mBbbN{}
5.  \mforall{}n:\mBbbN{}.  \mexists{}m:\mBbbN{}.  ((n  \mleq{}  m)  \mwedge{}  (y[n]  =  x[m]))  supposing  N1  \mleq{}  n
6.  \mforall{}k:\mBbbN{}\msupplus{}.  (\mexists{}N:\{\mBbbN{}|  (\mforall{}n:\mBbbN{}.  ((N  \mleq{}  n)  {}\mRightarrow{}  (|x[n]  -  a|  \mleq{}  (r1/r(k)))))\})
7.  k  :  \mBbbN{}\msupplus{}
8.  N  :  \mBbbN{}
9.  \mforall{}n:\mBbbN{}.  ((N  \mleq{}  n)  {}\mRightarrow{}  (|x[n]  -  a|  \mleq{}  (r1/r(k))))
\mvdash{}  \mexists{}N:\{\mBbbN{}|  (\mforall{}n:\mBbbN{}.  ((N  \mleq{}  n)  {}\mRightarrow{}  (|y[n]  -  a|  \mleq{}  (r1/r(k)))))\}


By


Latex:
(InstConcl  [\mkleeneopen{}imax(N;N1)\mkleeneclose{}]\mcdot{}  THEN  Auto)




Home Index